Perceived colour fidelity under LEDs with similar Rf but different Ra. (October 2019) - Wei, M; Royer, M; Huang, H-P
Substantial efforts have been made to develop new colour fidelity measures that are better correlated to perceived colour fidelity. Such measures minimize the possibility of increasing rated colour fidelity through spectral optimization without improving perceived colour fidelity. This paper reports a psychophysical experiment that was carefully designed to investigate how light sources with different spectral features affected perceived colour fidelity, and whether the effect can be reflected by the two existing colour fidelity measures (CIE R a and Illuminating Engineering Society (IES) R f ). Fourteen observers evaluated the colour differences of eight physical colour samples under three pairs of light sources, which had similar IES R f but different R a values. IES R f was found to perform better than CIE R a .